Monolayer Plasmonic Nanoframes as Large‐Area, Broadband Metasurface Absorbers. Issue 33 (20th July 2022) - Li, Yuanwei; Tanriover, Ibrahim; Zhou, Wenjie; Hadibrata, Wisnu; Dereshgi, Sina Abedini; Samanta, Devleena; Aydin, Koray; Mirkin, Chad A.
Abstract: Broadband absorbers are useful ultraviolet protection, energy harvesting, sensing, and thermal imaging. The thinner these structures are, the more device‐relevant they become. However, it is difficult to synthesize ultrathin absorbers in a scalable and straightforward manner. A general and straightforward synthetic strategy for preparing ultrathin, broadband metasurface absorbers that do not rely on cumbersome lithographic steps is reported. These materials are prepared through the surface‐assembly of plasmonic octahedral nanoframes (NFs) into large‐area ordered monolayers via drop‐casting with subsequent air‐drying at room temperature. This strategy is used to produce three types of ultrathin broadband absorbers with thicknesses of ≈200 nm and different lattice symmetries (loose hexagonal, twisted hexagonal, dense hexagonal), all of which exhibit efficient light absorption (≈90%) across wavelengths ranging from 400–800 nm. Their broadband absorption is attributed to the hollow morphologies of the NFs, the incorporation of a high‐loss material (i.e., Pt), and the strong field enhancement resulting from surface assembly. The broadband absorption is found to be polarization‐independent and maintained for a wide range of incidence angles (±45°). The ability to design and fabricate broadband metasurface absorbers using this high‐throughput surface‐based assembly strategy is a significant step toward the large‐scale, rapid manufacturing of nanophotonic structures and devices. Abstract : A strategy for synthesizing ultrathin (≈200 nm) metasurface broadband absorbers without the need for complex lithography is reported. Plasmonic octahedral nanoframes are assembled into ordered monolayers via drop‐casting and air drying at room temperature. The resultant metasurfaces exhibit polarization‐independent light absorption (≈90%) over a broad spectral range (400–800 nm) with limited dependency on the angle of incidence.